DEVELOPMENT OF SPSS PRACTICUM MODULE ON COURSES STATISTICS EDUCATION - Jawasi, Jawasi; Zulkardi, Zulkardi; Darmowijoyo, Darmowijoyo
This study aims to develop practical modules by utilizing SPSS software applications so that students can easily understand the learning on the statistics education course at Raden Fatah State Islamic University of Palembang. Type of research is research development or development research. This research will develop teaching materials in the form of a valid and practical Student Module in the course of Education Statistics, through two stages of preliminary study and formative study. The preliminary stage includes preparation and design, while the formative study stage includes Self Evaluation, Expert Reviews, One to One, Small Group and Field Test, taking samples of 20 semester 4 students on the Education Statistics course in Mathematics Education Study Program Raden Fatah State University Palembang. The results of the research are based on the preliminary study and formative study, and the average observation of the results is shown in the practical category of 82.58%, the SPSS Practicum Module can be used in the learning process in the Education Statistics Course.